Analisis Implementasi Undang Undang No 35 Tahun 2014 Tentang Perlindungan Anak Di Pondok Riyadlul Ba’diah - Alfadli, Veri; Wahyudi Gani, Andika; Rifdan, Rifdan (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2025)
This study aims to determine: (1) how the understanding of the ranks of educators of the Riyadlul Ba'diah Islamic boarding school in North Luwu is regarding the law on child protection (2) how the implementation of the law on child protection in the rules of the Riyadlul Ba'diah Islamic boarding school in North Luwu. This type of research is a qualitative approach with a field study method involving interviews with the boarding school administrators and teachers or educators at the Riyadlul Ba'diah Islamic boarding school in North Luwu. Data analysis uses data reduction, data presentation, and drawing conclusions related to the results of the study. The results of the study indicate that: (1) The understanding of the ranks of educators regarding the law on child protection (UU PA) at the Riyadlul Ba'diah Islamic boarding school is still limited and requires improvement. This limited understanding is caused by the lack of training, resources and government support. (2) in the rules of the Riyadlul Ba'diah Islamic boarding school, it does not meet the standards of child protection, with only 50% of the principles of child protection listed andonly a few educators understanding the rules. This study has implications in emphasizing the importance of understanding and implementing child protection laws in Islamic boarding schools.